Innovative Potential of Russian Regions: Analysis of Formation of Regional Clusters Connected by Technological Chains - Migunova Galina Stepanovna; Andrey Polyanin; Tatiana Popadyuk; Svetlana Valeryevna Poltoryhina (International Journal of Supply Chain Management, 2020)
The modern era is characterized by irreversible transformation processes of the economy. First, it is the fall in hydrocarbon prices, which will stimulate the weakening of the economies of oil and gas-dependent regions.Â  Secondly, the fourth technological order began to transform into the fifth, which means that the classical production instead of the main centers of value creation are transformed into engineering infrastructure. Third, the globalization of markets defeats any attempt to close borders, which means that in order to achieve success, it is initially necessary to focus on global highly competitive markets, not only on food, but also on labor, knowledge and technology markets.Correlation analysis shows that almost all countries of the world with a developed high-income economy, at the same time top the list of the most innovative States, which once again confirms the action of these trends.Analyzing the economic prospects of Russia, it is important to recognize that the rate of processing and export of petroleum products, the preservation and development of traditional industries, as well as the localization of supply chains are not able to provide the country with economic growth and bring it closer to the most developed economies of the world.In this article we consider innovative development of subjects of Russia. Problems and prospects of innovative development of real sector of economy of regions are revealed. Thus, thanks to a comprehensive study of the motives of global supply chains, recommendations are made for the creation of innovative clusters to improve the economy of Russian regions.